Wind Shear Coefficient Estimation Based on LIDAR Measurements to Improve Power Law Extrapolation Performance - Dragos Machidon; Marcel Istrate; Razvan Beniuga (Remote Sensing)
This study aims to improve power law extrapolation accuracy by proposing a new methodology for wind shear coefficient calculation. Real wind speed profiles, measured with a LIDAR remote sensor at two different sites, were extrapolated according to the power law at heights up to 200 m. Two different definitions of the wind shear coefficient are proposed considering wind speed profiles measured at three, four, and five different heights using either the first height as a reference or all of the heights successively. These two definitions were tested, along with the generally accepted constant values of 1/7, 0.25 at the first site, and 0.2 at the second site, to identify the most efficient one. The extrapolated wind profiles were compared with those measured using LIDAR. The results show that the computed wind shear coefficients provide more accurate results compared with constant wind shear coefficients, as the mean absolute errors at 200 m were reduced from 1.396 m/s to 0.437 m/s at the first site and from 1.203 m/s to 0.411 m/s at the second site.